Substance abuse and its relationship to emotional dependence, attachment and emotional regulation in adolescents - Momeñe, Janire; Estevez, Ana; Perez-Garcia, Ana Maria; Jimenez, Javier; Chavez-Vera, Maria Dolores; Olave, Leticia; Iruarrizaga, Itziar (Anales de Psicología / Annals of Psychology, 2021)
Substance use among adolescents is a serious social problem that may be related to emotional dependence, attachment styles and difficulties in emotional regulation. Thus, the objectives of this study were to analyse the relationship and predictive role of emotional dependence, attachment and emotional regulation on substance use in the last month. In addition, gender and age differences were analysed in all variables of the study. The mediating role of emotional regulation and attachment styles in the relationship between emotional dependence and substance use was also verified. The sample used was made up of 1.533 schooled adolescents, 826 men and 707 women with ages ranging from 13 to 22 years (M = 15.76, SD = 1.25). The results showed a positive relationship between substance use and emotional dependence. Similarly, substance users showed positive relationships with the difficulties of emotional regulation, as well as, with the attachment styles of parental permissiveness, self-sufficiency and resentment against parents and child trauma, and negative relationships with secure attachment, family concern, parental interference and value to parental authority.